Rossiia, torgovlia oruzhiem . Rossiia, torgovlia oruzhiem . Russia, Trade of Weapons . Россия, торговля оружием - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing Russian weapons exports. Featured in the program: IAnpol'skii, G. G. (Deputy Chairman of the Committee of the Russian Defense Industry) Contributors: Levchenko, Aleksandr (Anchor) В передаче обсуждается экспорт российского оружия. В программе участвуют: Янпольский, Г. Г. (Заместитель председателя комитета по оборонным отраслям промышленности России) Создатели: Левченко, Александр (Ведущий/Ведущая)